Incidence of complications in peripherally inserted central catheters in ambulatory oncology patients (Research, Society and Development, 2024)
Introduction: Intravenous therapy has become widely used in oncological treatments, such as for the administration of chemotherapy drugs, antibiotics, blood products, hydration, among others. Given this, devices for establishing an intravenous route have demonstrated great utility in oncology, including peripherally inserted central venous catheters, PICCs. Objective: to analyze the incidence of the main complications that contributed to the removal of PICC`s in the period from 2021 to 2022. Method: This is a retrospective cohort study, with a quantitative, descriptive and exploratory approach, based on data collected from a standardized instrument for controlling patient care. Results: the main reasons that led to the removal of catheters in the period analyzed, the end of treatment appears to be the most incident followed by infection. The total number of removals was 89 PICC`s, compared to the total number of insertions in the two years of 361 catheters. Infection was the main reason for removal associated with non-adherence to maintenance, corresponding to 30.7% in the 2021 group and 30% in 2022. Conclusion: there is a need for standardization of protocols related to the appropriate handling of the device by healthcare professionals. nursing, frequency of maintenance and guidance to patients and families.